Pengaruh Kualitas Layanan, Kepercayaan dan Keamanan Produk BSI Mobile terhadap Kepuasan Nasabah Bank Syariah Indonesia KCP Dhamasraya - Mahendra, Opi; Martilova, Novera (Lembaga Yasin AlSys, 2026)
Service quality, trust, and product security in mobile banking have received attention in various studies, but research specifically analyzing the influence of these three variables on customer satisfaction among BSI Mobile users at Bank Syariah Indonesia Dharmasraya Sub-Branch Office remains limited. This study aims to analyze the influence of service quality, trust, and BSI Mobile product security on customer satisfaction, both partially and simultaneously. This study used a quantitative approach with a survey design, involving 100 respondents selected through purposive sampling. Data were collected using a questionnaire developed based on the indicators of the research variables and were then analyzed using multiple linear regression with the assistance of the Statistical Package for the Social Sciences (SPSS) application. The results showed that service quality, trust, and product security had a positive and significant effect on customer satisfaction among BSI Mobile users. Service quality was the most dominant factor influencing customer satisfaction, with a regression coefficient of 0.352 and a significance level of 0.000. In addition, trust and product security were also proven to have a significant effect on customer satisfaction, with significance values of 0.000 and 0.002, respectively. The conclusion of this study affirms that improving digital service quality, strengthening customer trust, and ensuring electronic transaction security are important factors in increasing user satisfaction with mobile banking services in Islamic banking. These findings contribute to the development of studies on service quality, trust, and information system security in the context of Islamic banking digital services, while also providing practical implications for strengthening the quality of BSI Mobile services.